Transmission line protection challenges infuenced by inverter-based resources: a review - Quispe Huarcaya, Juan Carlos (2022)
High penetration of renewable energy sources (RES) leads to new challenges for protection devices. Protection schemes are typically designed according to the dynamic behavior of rotating machines as generation sources, while the RES dynamic response, mainly governed by inverters, is not considered. Consequently, some relevant algorithms of transmission line protection are experiencing challenges because of the fact that magnitude and phase angle comparison, amount of negative-sequence, and short-circuit current level are afected by the RES. Therefore, an in-depth study of this issue is necessary, one which considers the main causes and new methodological criteria solutions. This work presents an extensive literature review of the evaluation of electrical protection performance and the efects of RES connected to a power grid through inverters. Bibliographic data on many representative publications related to this topic are obtained to show the current research lines and their proposed solutions. In addition, this work identifes the main protection functions afected and describes the new protection schemes that consider RES. Finally, an analysis and discussion of the selected bibliography are presented.